Computational investigations into heat transfer over a double wedge in hypersonic flows - Expósito, Diego; Rana, Zeeshan (Elsevier, 2019)
Recently developed OpenFOAM application hy2FOAM is employed to predict the aerodynamic heat transfer numerically and compared with the experimental data from the University of Illinois. Mach 7 nitrogen flow at 2.1 MJ/kg stagnation enthalpy, and Mach 7 nitrogen and air flows at 8 MJ/kg stagnation enthalpy over a double wedge geometry have been reproduced numerically assuming chemical and thermal non-equilibrium. Good agreement of mean heat transfer profiles has been observed, although none of the simulations achieved a steady-state. The reattachment heat transfer peak in the high enthalpy air case showed an improved agreement with the experimental data, which is due to the non-equilibrium in the flow field.
Keywords: Heat transfer; Hypersonic flow; Double wedge; CFD; Boundary layer interactions; High enthalpy flow